2021
DOI: 10.3390/ma14092444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cr on Aqueous and Atmospheric Corrosion of Automotive Carbon Steel

Abstract: This study investigated the effect of Cr alloying element on the corrosion properties of automotive carbon steel (0.1C, 0.5Si, 2.5Mn, Fe Bal., composition given in wt.%) in aqueous and atmospheric conditions using electrochemical measurement and cyclic corrosion tests. Three steels with 0, 0.3, and 0.5 wt.% Cr were studied by electrochemical impedance spectroscopy. Polarization resistance (Rp) of 0.3 Cr and 0.5 Cr steels was higher than that of 0 Cr steel, and the Rp also increased as the Cr content increased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…When β-FeOOH comes into contact with water, it releases Cl − ions. The dissolved Cl − ions then undergo hydrolysis reactions with Fe 2+ and Cr 3+ , causing a reduction in the pH of the steel surface [8]. Due to these characteristics, the region where β-FeOOH is formed can be considered a Cl-concentrated region.…”
Section: Minimum Cct Cycles For Localized Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…When β-FeOOH comes into contact with water, it releases Cl − ions. The dissolved Cl − ions then undergo hydrolysis reactions with Fe 2+ and Cr 3+ , causing a reduction in the pH of the steel surface [8]. Due to these characteristics, the region where β-FeOOH is formed can be considered a Cl-concentrated region.…”
Section: Minimum Cct Cycles For Localized Corrosionmentioning
confidence: 99%
“…Cr-goethite blocked the diffusion of ions from the outside of Cr-goethite to the inside and vice versa. Therefore, Cl − ions that were transported through the defects of Cr-goethite or released when β-FeOOH was wet accelerated localized corrosion via autocatalytic reaction [8]. In addition, Cr 3+ has vital hydrolyzing characteristics, which induce a further pH decrease, causing the fast progression of localized corrosion [10].…”
Section: Minimum Cct Cycles For Localized Corrosionmentioning
confidence: 99%
“…At this time, the slope of the mass loss regression equation for nth condition is called An, and the slope of the corrosion depth regression equation for nth condition is called Bn. The uniform corrosion acceleration coefficient (α1) and localized corrosion acceleration coefficient (α2) are calculated using Equations ( 4) and (5).…”
Section: Uni F Orm Corrosion Depthmentioning
confidence: 99%
“…These variations can lead to micro-galvanic and localized corrosion issues in CP steel under atmospheric conditions. Notably, recent studies have reported that chromium (Cr) can increase localized corrosion in low-alloy steels under atmospheric corrosion conditions [5][6][7]. To address this concern, CP steel variants without Cr have been developed.…”
Section: Introductionmentioning
confidence: 99%